An ultra-thin multi-layered metamaterial for power transformer noise absorption. Issue 1 (March 2022) - Sharafkhani, Naser
A compact multi-layered structure is proposed based on the coiled-up space concept for power transformer noise absorption at 100 and 200 Hz. Current methods of constructing multi-band absorbers are impractical for power transformer noise control due to the high coupling effect deteriorating their performance. To overcome this shortcoming, the proposed structure is composed of multiple connected layers creating two separate coiled ducts with adjustable dimensions to minimise the coupling effect. In the modelling stage, the geometrical features are optimised using the genetic algorithm to maximise the absorption coefficient and minimise the thickness. The proposed dual-tone absorber has a thickness of 43.5 mm which is significantly thinner than the existing conventional absorbers. The measurement results on a 3D-printed structure demonstrate the feasibility of the design.